Evaluation of reopening of signalized intersections at Katipunan Avenue - Azucena, Maryam Jazzmine D.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Katipunan A venue is an arterial road that is surrounded by commercial establishments and three universities. Because of this, large volume of vehicles has led to heavy traffic congestion especially during peak hours. The traffic scheme has shifted from signalized intersection to U-turn scheme in 2003 and then from U-turn scheme to signalized intersection this 2014. There has been a debate of whether the recent change of traffic scheme has improved or worsened the traffic flow along Katipunan Avenue. Therefore this study aimed to compare the traffic conditions before and after the implementation of signalized intersections. The parameters that will be considered will be the travel time along the study area, the level of service, the degree of congestion at an intersection and the number of accidents. An actual field measurement was conducted to obtain the travel time. The average travel speed was used to get the level of service. The number of accidents were obtained from the MMDA Road Safety Unit and were summarized in order to determine the rate of accidents. The type and location of accidents were also observed. The results showed that for 2015, there is no significant change in the travel time and level of service during the morning peak hour. However, the level of service for the afternoon peak hour reached LOS F. The current degrees of congestion at the intersection are both greater than 1. However, there is a relative decrease in the rate of accidents at the road section and a significant decrease at the intersection. Based on the results, the change in traffic scheme may have worsened the traffic condition but improved the road safety.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Signalized intersections -- Philippines -- Quezon City; Roads -- Interchanges and intersections